PENGARUH LATIHAN TRAINING RESISTANCE XANDER DAN RESERVE CROSSOVER TERHADAP KEMAMPUAN KECEPATAN TENDANGAN SABIT - Amelia, Amelia; Adityatama, Firman; Hadiana, Oman (STKIP Melawi, 2024)
Abstract: The purpose of this study was to compare the effectiveness of TRX training and RC training on the ability of the crescent kick. This study is an experimental method. The subjects of this study were 16 athletes. The results of the t-test study on TRX training obtained a t count of 13,332 and a t table of 4,785 with a sig value of 0.000. The results of the t-test study on RC training obtained a t count of 5,495 and a t table of 4,785 with a sig value of 0.001. So there is a significant increase in the speed of the crescent kick. The magnitude of the increase in TRX and RC training, which can be seen in the t count value (TRX) 13,332 t count (RC) 5,495 is greater than the t table 4,024 (TRX 13,332> 4,024) (RC 5,495> 4024) with a significant value of TRX = 0.000, RC = 0.001 is smaller than 0.05 (sig <0.05) And the results of the effectiveness using a comparison of means on TRX and RC training. The mean test results on the TRX training mean test = 24.63, and on the RC training mean test = 20.75. The results of the comparison test mean TRX and RC training (24.63> 20.75) and the results of the Xander Resistance Training exercise are more significant because the results of the mean test are greater than the Reserve Crossover (Zigzag Run) exercise.Keywords: Xander Resistance Training Exercise and Reserve CrossoverÂ Abstrak: Tujuan penelitian ini adalah untuk mengetahui perbandingan efektivitas antara latihan TRX dan latihan RC terhadap kemampuan tendangan sabit. Penelitian ini merupakan metode eksperimen. Subjek dari penelitian ini adalah 16 atlet. Hasil penelitian uji-t pada latihan TRX diperoleh t hitung 13.332 dan t tabel sebesar 4.785 dengan nilai sig 0,000. Dan hasil penelitian uji-t pada latihan RC diperoleh t hitung 5.495 dan t tabel 4.785 dengan nilai sig 0,001. Sehingga terdapat peningkatan yang signifikan terhadap kecepatan tendangan sabit. Besarnya peningkatan dari latihan TRX dan RC, yang mana dapat dilihat pada nilai t hitung (TRX) 13.332 t hitung (RC) 5.495 lebih besar dari pada t tabel 4.024 (TRX 13.332 > 4.024) (RC 5.495 > 4024) dengan nilai signifikan TRX= 0,000, RC= 0,001 lebih kecil daripada 0,05 (sig<0,05) Dan hasil efektivitas menggunakan perbandingkan mean pada latihan TRX dan RC. Hasil uji mean pada latihan TRX uji mean = 24.63, dan pada latihan RC uji mean = 20.75, maka hasil dari ujibanding mean latihan TRX dan RC (24.63 > 20.75) maka hasil dari latihan Training Resistence Xander lebih signifikan karena hasil uji mean lebih besar dibandingkan dengan latihan Reserve Crossover (Zigzag Run).KataKunci: Latihan Training Resistance Xander dan Reserve Crossover